2015
DOI: 10.1186/s13287-015-0141-y
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells isolated from human dental pulp and amniotic fluid improve skeletal muscle histopathology in mdx/SCID mice

Abstract: IntroductionDuchenne muscular dystrophy (DMD), caused by a lack of the functional structural protein dystrophin, leads to severe muscle degeneration where the patients are typically wheelchair-bound and die in their mid-twenties from cardiac or respiratory failure or both. The aim of this study was to investigate the potential of human dental pulp stem cells (hDPSCs) and human amniotic fluid stem cells (hAFSCs) to differentiate toward a skeletal myogenic lineage using several different protocols in order to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…Combination with functional innervation and vascularization appears more persuasive for functional pulp regeneration. 107 118 Additionally, predifferentiated PSCs, including hepatocytes, 125 myocytes, 128 osteoblasts, 143 islet-like cell cluster, 45 and keratocytes, 137 Table 3, such as calvarial defect, 110 cerebral ischemia, 116,117 and limbal stem cell deficiency, 38 It was also reported that SHED are capable of differentiating into hepatocyte-like cells directly without fusion in mouse models of carbon tetrachloride-induced liver fibrosis, therefore recovering liver disfunction. 41 In a recent mouse in vivo study, 12…”
Section: Exogenous Recombinant Growth Factors a Variety Of Exogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination with functional innervation and vascularization appears more persuasive for functional pulp regeneration. 107 118 Additionally, predifferentiated PSCs, including hepatocytes, 125 myocytes, 128 osteoblasts, 143 islet-like cell cluster, 45 and keratocytes, 137 Table 3, such as calvarial defect, 110 cerebral ischemia, 116,117 and limbal stem cell deficiency, 38 It was also reported that SHED are capable of differentiating into hepatocyte-like cells directly without fusion in mouse models of carbon tetrachloride-induced liver fibrosis, therefore recovering liver disfunction. 41 In a recent mouse in vivo study, 12…”
Section: Exogenous Recombinant Growth Factors a Variety Of Exogenousmentioning
confidence: 99%
“…Differentiated dopaminergic neuron‐like SHED have been reported to survive in striatum of PD mice, significantly improve dopamine level and fiber sprouting in contrast to undifferentiated SHED and enhance neurological recovery . Additionally, predifferentiated PSCs, including hepatocytes, myocytes, osteoblasts, islet‐like cell cluster, and keratocytes, have been administered with therapeutic benefits in animal models for liver fibrosis, muscular dystrophy, calvarial bone defect, diabetes, and corneal trauma, respectively. It is indicated that transplantation of preinduced or predifferentiated PSCs appears more efficacious and more applicable to enhance functional recovery as compared with undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) were originally isolated from bone marrow (Friedenstein et al, 1970). MSCs are fibroblast-like cells capable of adhering to plastic dishes, to form colonies derived from single cells (colony forming unit fibroblasts), and to differentiate into mature cells of mesenchymal lineages such as osteoblasts and chondrocytes (Caplan and Bruder, 2001;Friedenstein et al, 1970;Pittenger et al, 1999;Prockop, 1997;Sudo et al, 2007;Weissman et al, 2001). The discovery that human adult teeth contain cells with similar functions to MSC indicated that these organs are important reservoirs of adult stem cell populations .…”
Section: Stem Cells Within Teethmentioning
confidence: 99%
“…Due to the lack of specific DMSCs markers, generic MSC markers such as STRO-1, CD146 and CD44 are commonly used for the isolation and identification of DMSCs (Pittenger et al, 1999). DPSCs are capable of differentiating into odontogenic Hayashi et al, 2015;Miura et al, 2003), osteogenic (d'Aquino et al, 2009;de Mendonca Costa et al, 2008), chondrogenic (Waddington et al, 2009), adipogenic Waddington et al, 2009), myogenic (Kerkis et al, 2008Pisciotta et al, 2015), and neurogenic (Martens et al, 2014;Nosrat et al, 2001) …”
Section: Ta Mitsiadis Et Al Stem Cells For Dental Clinical Usementioning
confidence: 99%
“…Particularly, dental pulp stem cells can be obtained through non‐invasive procedures, exert immunomodulatory properties and are able to differentiate towards different lineages. Previous findings demonstrated that hDPSCs are able to participate to the regeneration of skeletal muscle in Duchenne Muscular Dystrophy (DMD) and peripheral nerve injury animal models after reaching the commitment towards myoblasts and Schwann cells, respectively . Even though hDPSCs were investigated in the regeneration of bladder smooth muscle, less is known about their application in animal model of SUI.…”
Section: Introductionmentioning
confidence: 99%